“Heroic Souls”: Representations of the Black Female Heroism of Harriet Tubman and Sojourner Truth - James, Charlotte (2022)
This thesis is the first research project to provide a thorough examination of the memory of Harriet Tubman and Sojourner Truth, exploring portrayals of their heroism and considering how such depictions impact our understandings of Black female heroism. Tubman and Truth frequently appear together in representations, but scholars are yet to analyse how these Black women have become heroes, with no thorough examination of how depictions of their heroism interact and impact upon one another. In providing the first comprehensive analysis and comparison of Tubman and Truth’s memory from the late 1930s to present day, this thesis highlights how current understandings of Black female heroism are defined by prevailing ideas of white and Black male heroism. Through analysis of a variety of representations, such as artwork (including murals and sculptures), theatre productions, poems, and film, this thesis argues for a re-evaluation of Black female heroism and presents a new model that centres around Black women’s experiences, with recognition of their triple oppression and the different forms of resistance they employed, including those performed by “ordinary” Black women. By exploring how Tubman and Truth’s memory struggles against hegemonic ideas of heroism, I examine alternative heroic behaviours that centre around Black women’s resistance, such as anti-lynching activism and trade union organising, to expand our understandings of who is deemed heroic. Moreover, in analysing Tubman and Truth’s persistent role as Black female heroes, I offer vital insight into the limitations of existing depictions, with representations often shaped and limited by concepts of exceptionality and acceptability. Throughout the following chapters, I examine how portrayals of Tubman and Truth as “superwomen” who overcome overwhelming oppression maintain ideas of exceptionalism, noting how their depiction as Moses and a religious preacher further supports this limiting framework. In analysing depictions of Tubman and Truth’s militancy, this research also considers how ideas of acceptability narrow our understandings of their heroism, thus noting how exceptionalism and acceptability can obscure features of Tubman and Truth’s lives and memories, whilst also contributing to the erasure of “ordinary” Black women and their heroic behaviours. Through this research, I also examine the instances in which artists and writers challenge the confines of exceptionality and acceptability, arguing that these portrayals create an alternative heroic lineage that positions Tubman and Truth alongside other Black women, while also highlighting the latter’s malleability as a Black female hero. Indeed, in prioritising Black women’s experiences and recognising their triple oppression, I argue that these artists and writers broaden our understandings of Black female heroism. Thus, in examining the different ways in which Tubman and Truth are portrayed as heroes across the twentieth and twenty-first centuries, this thesis develops a model of Black female heroism that allows for better understanding of the ways in which Black women are remembered.